Randomized feasibility trial of the Scleroderma Patient-centered Intervention Network hand exercise program (SPIN-HAND): study protocol - Carrier, Marie-Eve (2018)
Background: Significant functional impairment of the hands is nearly universal in systemic sclerosis (SSc, scleroderma). Hand exercises may improve hand function, but developing, testing and disseminating rehabilitation interventions in SSc is challenging. The Scleroderma Patient-centered Intervention Network (SPIN) was established to address this issue and has developed an online hand exercise program to improve hand function for SSc patients (SPIN-HAND). The aim of the proposed feasibility trial is to evaluate the feasibility of conducting a full-scale randomized controlled trial (RCT) of the SPIN-HAND intervention. Design and methods: The SPIN-HAND feasibility trial will be conducted via the SPIN Cohort. The SPIN Cohort was developed as a framework for embedded pragmatic trials using the cohort multiple RCT design. In total, 40 English-speaking SPIN Cohort participants with at least mild hand function limitations (Cochin Hand Function Scale ≥3) and an indicated interest in using an online hand-exercise intervention will be randomized with a 1:1 ratio to be offered to use the SPIN-HAND program or usual care for 3 months. The primary aim is to evaluate the trial implementation processes, required resources and management, scientific aspects, and participant acceptability and usage of the SPIN-HAND program. Discussion: The SPIN-HAND exercise program is a self-help tool that may improve hand function in patients with SSc. The SPIN-HAND feasibility trial will ensure that trial methodology is robust, feasible, and consistent with trial participant expectations. The results will guide adjustments that need to be implemented before undertaking a full-scale RCT of the SPIN-HAND program. Trial registration: ClinicalTrials.gov Identifier: NCT03092024.